Pilocytic astrocytoma of sellar/suprasellar region determining endocrine manifestations - Eduardo Cambruzzi; Karla Lais Pêgas; Luciano Carvalho Silveira (Sociedade Brasileira de Patologia Clínica, 2013)
Pilocytic astrocytoma (PA) is a grade I glial neoplasm arising mainly in the cerebellum of children. Herein, the authors report a case of PA in a 21 year-old male patient, who presented headache, vomiting and delayed pubertal development. Serum level of cortisol and testosterone corresponded to 32.8 ug/dl and 0.19 ng/ml, respectively. The computed tomography/magnetic resonance (CT/RM) imaging showed an expansive process compromising suprasellar/hypothalamic region and determining hydrocephalus. The patient underwent resection of the process. Histological evaluation revealed a glial neoplasm constituted by loose glial tissue, small microcysts, areas of dense piloid tissue and Rosenthal fibers. The neoplastic cells were immunoreactive for glial fibrillary acidic protein (GFAP) and negative for chromogranin and synaptophysin. The diagnosis of PA was then established.